2007
DOI: 10.1620/tjem.211.133
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Vagal Activation by Adrenocorticotropic Hormone Treatment in Infants with West Syndrome

Abstract: West syndrome (WS) is a generalized epileptic syndrome of infancy and early childhood with various etiologies, and consists of a triad of infantile spasm, arrest or regress of psychomotor development and specific electroencephalogram (EEG) pattern of hypsarrhythmia. WS had been believed to be refractory, but recent evidence supports effectiveness of adrenocorticotropic hormone (ACTH) treatment. The ACTH treatment, however, has a problem that it is often accompanied by adverse autonomic symptoms. We therefore e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 32 publications
1
27
2
Order By: Relevance
“…Heart rate variability analysis has been advocated in the literature as a noninvasive measure of autonomic function (15,16,22,44) and was used to provide multiple temporal measures of cardiac autonomic function over the duration of the seizure response. Importantly, to the best of our knowledge, this is the first time HRV has been used to assess cardiac control in a rat model of seizure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart rate variability analysis has been advocated in the literature as a noninvasive measure of autonomic function (15,16,22,44) and was used to provide multiple temporal measures of cardiac autonomic function over the duration of the seizure response. Importantly, to the best of our knowledge, this is the first time HRV has been used to assess cardiac control in a rat model of seizure.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in HR variability (HRV), a noninvasive index of autonomic activity, have been reported in individuals with epilepsy (16). HRV analysis has demonstrated both sympathetic (1,10,15) and parasympathetic (43,54,71) dominance in patients with TLE, whereas generalized tonicclonic seizures are associated primarily with sympathetic dominance (15,16,22,44).…”
mentioning
confidence: 99%
“…HRV parameters were found to be altered in various disorders, such as diabetic neuropathy (Bernardi et al 1992), heart failure (Saul et al 1988), preeclampsia (Yokusoglu et al 2009), acute leukemias (Nevruz et al 2007), depletion anemias (Yokusoglu et al 2007a), fetal type Minamata disease (Oka et al 2002), in preschool children with short nocturnal sleep (Sampei et al 2006), primary nocturnal enuresis (Dundaroz et al 2001;Unalacak et al 2004), cardiac resynchronization therapy (Akyol et al 2006) and during adrenocorticotropic hormone replacement treatment in infants with West syndrome (Hattori et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, decrease in HRV was suggested to predict coronary heart disease morbidity and mortality in patients after an acute coronary event (Odemuyiwa et al 1991). Moreover, HRV parameters were found to be altered in various disorders such as diabetic neuropathy (Kitney et al 1982), heart failure (Saul et al 1988), acute leukemias (Nevruz et al 2007), allergic rhinitis , fetal type Minamata disease (Oka et al 2002), in preschool children with short nocturnal sleep (Sampei et al 2006), primary nocturnal enuresis (Dundaroz et al 2001;Unalacak et al 2004), following a cardiac transplantation (Sands et al 1989) or cardiac resynchronization therapy (Akyol et al 2006) and during adrenocorticotropic hormone replacement treatment in infants with West syndrome (Hattori et al 2007). Veglio et al (1998) reported decreased sympathetic activity in patients with thalassemia major.…”
Section: Discussionmentioning
confidence: 99%